Legal Protection for Commercial Sex Workers as Victims of Sexual Violence in Surabaya - Hadi Widodo Saputro; Gelar Ali Ahmad (Universitas Negeri Surabaya, 2025)
Commercial sex workers (CSWs) are vulnerable to sexual violence as they engage in a profession that involves providing sexual services to meet the biological needs of their clients. However, crimes often occur outside the agreed-upon terms or in cases where no agreement on the exchange of services has been made, resulting in harm to workers who often engage in CSW due to economic necessity. Thus, clear and robust legal protection is necessary to maximize justice and achieve legal certainty as the aim of criminal law for both victims and non-victims, thus minimizing future incidents. This research employs an empirical juridical method, utilizing an online questionnaire distributed through social media platforms such as Twitter and Instagram to collect data, as well as conducting direct interviews with victims and law enforcement personnel to gain accurate information based on field observations. The results include various forms of protection afforded to the victims, as well as an explanation of the challenges faced during the awareness-raising process within the community regarding sexual violence. This high level of awareness is crucial to ensure that individuals are no longer indifferent or ashamed to protect or assist close relatives who may be victims of sexual violence within their immediate communities. Especially in Surabaya.